The development of PROQOL-HIV: An international instrument to assess the health-related quality of life of persons living with HIV/AIDS - Duracinsky M. (2017)
Objectives: Health-related quality of life (HRQL) is an important outcome in HIV/AIDS infection and treatment. However, most existing HIV-HRQL instruments miss important issues (eg, sleeping problems, lipodystrophy). They were developed before highly active antiretroviral therapy (pre-HAART), and in a single language. We sought to develop a contemporary HIV-HRQL instrument (PROQOL-HIV) in multiple languages that accounts for HAART treatment and side effects. This article details the 3-stage content validation phase of PROQOL-HIV. Methods: In stage 1, we developed a conceptual model of HIVHRQL and questionnaire item bank from thematic analysis of 152 patient interviews conducted simultaneously across 9 countries. In stage 2, pilot items were selected by an expert panel to form the pilot instrument. Stage 3 involved linguistic validation and harmonization of selected items to form an equivalent instrument in 9 target languages. Results: Analysis of 3375 pages of interview text revealed 11 underlying themes: general health perception, social relationships, emotions, energy/fatigue, sleep, cognitive functioning, physical and daily activity, coping, future, symptoms, and treatment. Seven issues new to HIV-HRQL measurement were subsumed by these themes: infection fears, future concerns, satisfaction with care, self-esteem problems, sleep problems, work disruption, and treatment issues. Of the 442 theme-related items banked, 70 items met the retention criteria and formed the pilot PROQOL-HIV instrument. Conclusions: HIV patients across 11 countries attributed a wide range of physical, mental, and social issues to their condition, many of which were not measured by existing HIV-HRQL instruments. The pilot PROQOL-HIV instrument captures these issues, is sensitive to sociocultural context, disease stage, and HAART. © 2012 Lippincott Williams & Wilkins.